Physical Activity and Associated Factors in Indonesian Patients with Acute Myocardial Infarction - Ismail Fahmi; Elly Nurachmah; Sri Yona; Tuti Herawati (Mashhad University of Medical Sciences, 2023)
Background: Acute Myocardial Infarction (AMI) patients generally report persistent symptoms such as pain, fatigue, depression, and disorders in fulfilling daily needs. Physical activity has a beneficial effect on cardiopulmonary rehabilitation and remodeling of dysfunction after AMI.Aim: This study was performed aimed to identify physical activity and related factors in AMI patients.Method: This cross-sectional study was performed on 150 post-treatment AMI patients who were discharged from a central hospital in Indonesia from February to March 2019. The physical activity data were collected using the International Physical Activity Questionnaire. Depression was measured using the PHQ-9 Patient Depression Questionnaire, and self-efficacy using the Cardiac Self-Efficacy Scale. Data were analyzed by SPSS software (version 26.0) and Chi-square and fisher's exact tests. P<0.05 was considered statistically significant.Results: After hospitalization, majority of patients were in adult age (<60 years old) category (73.3%), were male (78.8%), had passed 7 to 30 days post-discharge (75.3%), and had comorbidities (64.7%). The majority of patients had mild physical activity (82%), in the mild depression category (69.3%), and had negative self-efficacy (86.7%). Factors related to low physical activity were age (P=0.002), gender (P=0.0001), days after hospitalization (P=0.03), comorbidities (P=0.02), depression (P=0.003), and self-efficacy (P=0.0001). The logistic regression test showed that age, gender, and self-efficacy improve physical activity in post-discharge AMI patients.Implications for Practice: Age, gender, and self-efficacy can enhance physical activity in post-discharge AMI patients. It is suggested that a pre-discharge and follow-up education be performed to evaluate physical activity.